Informação e arte: memórias e representação do acervo do Núcleo de Arte Contemporânea na Paraíba - Catoira, Thaís (2012)
This survey seeks to establish relationships with different knowledge areas, like the Information Science, Visual Arts and the Social Memory, through technical and methodological tools, as well as, from organization models, aimed at treatment of the acquis of the Contemporary Art s Core of Paraíba NAC/UFPB, composed of a variety of informational sources, related to contemporary art. Taking as a basis the discussion about the relationship between information and memory and seeking to understand these phenomena from the study and of the classification and representation of the acquis of NAC. In order to constitute the representation of information with a view to their recovery, through informational signs, aiming a re-meaning of the incorporated memories of the Core throughout its existence. Noting the specific problems and issues brought by the organization of a collection of contemporary art, based on Becker (1997), in instruments of documentary hypothesis analysis, through the informational structures of objects, and still in the goals and perspectives of the Information Science today, the methodological procedures adopted provided structuring a model organization itself, who systematized and presented more dynamically the information contained in the acquis, retrieving them and constituting new meanings to the memory of the NAC/UFPB.